Contact Dermatitis Caused by Dermabond Advanced Use. Issue 9 (September 2018) - Nakagawa, Shiho; Uda, Hirokazu; Sarukawa, Shunji; Sunaga, Ataru; Asahi, Rintaro; Chi, Daekwan; Yoshimura, Kotaro
Abstract : Background: Dermabond Advanced (DBA) has been widely used globally; however, severe contact dermatitis (CD) can be a serious adverse effect of DBA use. In this study, we investigated the characterization and incidence rate of CD after using DBA and the safe use of DBA. Methods: One hundred consecutive patients who underwent skin closure with DBA were investigated. All patients were women undergoing breast reconstruction. DBA was applied to their trunk and limbs following reconstruction. Results: Seven patients (7%) presented with CD. Of these, 4 patients exhibited CD after the second DBA use; sensitization influence by the first DBA use was considered. One of 3 patients presenting with CD after the first DBA use was allergic to cosmetic glue, and the influence of immunological cross-reaction of acrylates was suggested. Conclusion: We consider that DBA use is inadequate for wounds with an improper margin and in dry and low-skin barrier areas such as the trunk and limbs because it may induce irritant CD and sensitization of DBA and subsequent allergic CD. Frequent use can also induce sensitization. If patients have a history of acrylate allergies, DBA use should be avoided because immunological cross-reaction from acetylates could result.